Distribution Patterns and Spatial Relationships in the Perspective of Tourism Destination Typology - Anak Agung Sagung Alit Widyastuty; Siti Nuurlaily Rukmana; Moch Shofwan; Anak Agung Gede kamajaya Waisnawayadnya (Local Wisdom : Jurnal Ilmiah Kajian Kearifan Lokal, 2024)
Gianyar Regency, as one of Bali’s leading tourist regions, continues to develop tourism destinations in support of the regional tourism development plan and vision of “Realizing High-Quality, Competitive, Sustainable, and Prosperous Cultural Tourism.” The development of Gianyar Regency’s tourism potential requires an understanding of the spatial relationships based on the typology and distribution patterns of tourism destinations. This research aimed to reveal the typology of tourism destinations in Gianyar Regency, determine the distribution patterns of tourism destinations in Gianyar Regency, and assess spatial relationships in Gianyar Regency based on the typology and distribution patterns of tourism destinations. The research method employed in this study is qualitative descriptive, Near Neighbour Analysis (NNA), and Linkage system analysis. The typology of tourism destinations in Gianyar Regency includes cultural tourism, marine tourism, and natural reserve tourism. The distribution pattern of cultural and marine tourism destinations is clustered, while natural reserve tourism exhibits a random distribution pattern. Overall, tourism destinations in Gianyar Regency have a clustered distribution pattern. Spatial relationships in Gianyar Regency, based on the typology and distribution patterns of tourism destinations, are visually characterized by linear elements such as roads, corridor elements like buildings and trees, and side elements consisting of variations in tourism typology. The collective spatial relationships found in Gianyar Regency fall into an open-ended group form. The policy implications of this research suggest the need for improvements in tourism infrastructure and the development of spatial relationships to enhance the tourist experience, supporting sustainable tourism development in Gianyar Regency